Glacier retreat and melt-lake expansion at Stephenson Glacier, Heard Island World Heritage Area - Kiernan, K; McConnell, A (2002)
Historical records, recent observations, and geomorphological evidence indicate that rates of retreat and downwasting of the tidewater Stephenson Glacier, and concurrent expansion of ice-marginal melt-lakes, has increased by an order of magnitude since 1987. Melt-lake expansion is partly the product of greatly accelerated ablation of older, ice-cored twentieth-century moraines. The timing of these changes broadly coincides with reported increases in atmospheric and sea-surface temperatures around other sub-Antarctic islands, but correlates less well with changes along the northern Antarctic Peninsula, where warming has been more rapid. These recent changes in landscape character and geomorphological processes have implications for geodiversity, biodiversity, and cultural heritage values in this World Heritage Area. If the causal climatic warming is anthropogenic, it reinforces the fact that even the most remote and little-visited nature conservation reserves may be compromised by off-site human impacts, confronting management authorities with difficult philosophical and practical issues.